Water quality and the presence of metals in crustaceans (Sartoriana spinigera) and mollusks (Pila globosa) close to an urban waste landfill in Kodda at Gazipur - Mondal, Md Nurunnabi; Siddiqui, D M Rokibul Hoque; Promi, Israth Jarin; Ahsan, Md Emranul; Choudhury, Tasrina Rabia; Abrarin, Shaifa (Annals of Bangladesh Agriculture, 2023)
Degradation of water and sediment quality along with other aquatic ecosystem components, due to urban waste is a significant concern that demands attention. Despite of the multifaceted use of the Konabari area within the Gazipur City Corporation of Bangladesh, limited studies have assessed the health of the floodplain ecosystem adjacent to urban waste landfills in Kodda. This research focuses on evaluating water quality parameters and the presence of metals and metalloids in water, sediment, and biota (invertebrates) in the lowland floodplain near the Kodda municipal landfill in Gazipur district. In December 2022, thirteen composite samples, including water, sediment, crustaceans (Sartoriana spinigera), and mollusks (Pila globosa), were collected from the designated sampling site. Surface and sub-surface (0–15 cm depth) water were collected using a water sampler for water quality analysis, and the presence of heavy metal and metalloid content of the water, sediment, crabs, and mollusks were analyzed using an atomic absorption spectrometer. The results indicated dissolved oxygen concentrations ranging from 0.30 to 5.81 mg/l (mean 3.1±2.37 mg/l). Certain locations directly affected by waste discharge exhibited alarmingly low dissolved oxygen levels ( 0.71 mg/l), coupled with elevated temperatures and phosphate (PO43−) content (2–7.4 mg/l). The scarcity of heavy metal concentrations (<0.0677 mg/l) in water may be attributed to the constant flow of water preventing metal accumulation in the flowing water. However, sediment analysis revealed significantly higher concentrations (mean±Sd) of Fe (15240±1211 mg/kg), Mn (1122±180 mg/kg), Cu (44±5.5 mg/kg), Cr (28±3.2 mg/kg), Ni (39±2.4 mg/kg), As (3.7±0.89 mg/kg), and Zn (72±3.95 mg/kg) compared to other studies in various locations. Crustacean (Crab) samples showed concentrations of Cr, As, Pb, Cd, Zn, and Cu exceeding recommended permissible limits. Pila globosa emerged as an effective ecological bioindicator of aquatic pollution, with concentrations of Cr, Mn, Ni, Cu, Zn, and Pd exceeding recommended limits. Despite eco-environmental indices suggesting low to moderate contamination, the heavy metals and metalloids study indicated degradation of ecosystem health triggered by urban waste discharge. Consequently, the study recommends proper waste treatment in landfills and their transformation from open dumps to scientifically managed controlled waste landfills. Ann. Bangaldesh Agric. 27(2):175-189